A patient navigation initiative to improve access to breast cancer care in Cali, Colombia. Issue 9 (1st November 2021) - Perez‐Bustos, Andres H.; Orozco‐Urdaneta, Mavalynne; Erazo, Raúl; Cordoba‐Astudillo, Patricia; Gallo, David; Muñoz‐Zuluaga, Carlos; Sittig, Michelle; Sardi, Armando
Abstract: Background: Patient navigation is the logistical and emotional support necessary to achieve diagnostic and treatment compliance. It can improve time to diagnosis, initiation of treatment, and patient satisfaction, as well as reduce the cost of treatment. Colombia has a well‐defined Cancer Control Plan, but its implementation is lacking. Aim: To implement the first patient navigation initiative in Colombia, as part of a pilot program for the early detection of breast cancer. Methods: The process involved assessing and addressing the barriers faced by women to access breast health care by providing training for health personnel, strengthening primary health care providers, and coordinating diverse level institutions for the provision of services. This led to the design and implementation of a navigation strategy focused on the needs of patients in Cali, Colombia and the involvement of the local health system to provide such services. Results: Time to diagnosis was significantly reduced; research advanced by the Colombian National Institute of Cancerology shows that the average time between the first medical consultation and diagnosis was 91 days (CI 95%: 82–97 days), while this study carried out the same process in an average of 30 days, but patients still had issues with continuity of treatment due to financial strain between healthcare providers and insurers. Navigation, however, manages to overcome many of these problems by assisting women in the clinical and administrative care processes and seeking well‐being for the beneficiaries. In addition, patient navigation helped identify critical failures in care, such as fragmentation of care and excessive bureaucracy. The navigation process improved data collection and established agreements to simplify and make the delivery of care more efficient. In addition, it generated partnerships between service providers and insurers. Conclusion: While several barriers and poor understanding of the navigation process still exist, a navigation program can help implement a Cancer Control Plan.